Signature Events: The Role of Representative Major Events for the Branding of Catholic Pilgrimage Sites (Germany) - Markus Hilpert (International Journal of Religious Tourism and Pilgrimage, 2022)
A new trend in destination marketing has been emerging for several years. Instead of many small events, locations rely on one brand-strengthening Signature Event that draws attention to the destination through its uniqueness. Because pilgrimage is arguably the oldest form of mass tourism, places of pilgrimage may have invented such Signature Events to attract devout travellers. If so, signature events at pilgrimage sites are valuable research objects for investigating their success factors. Not only are they the prototypes in which the DNA of Signature Events can be studied, but in many cases, they also had centuries to optimise their experience. Using the example of the most visited Catholic pilgrimage sites in Germany, this research examines whether there are signature events, what common structures they have, and what can be derived from these findings for destination marketing.